213k views
5 votes
Find the distance between the points (-9,-7) and (2,-6)

User DjP
by
5.0k points

2 Answers

5 votes

To solve this problem, we need to use the distance formula.

Distance =
√((x2 - x1)^2 + (y2 - y1)^2)

x1 = -9

x2 = 2

y1 = -7

y2 = -6

Plug your numbers in

Distance =
√(((2) - (-9))^2 + ((-6) - (-7))^2). Simplify each parenthesis.

Distance =
√(121 + 1). Add these numbers together and take the square root.

Distance = √(122) or 11.05 units.

User Agyemang
by
5.0k points
3 votes

Answer:


√(122)

subtract the x from the other x and the y from the other y. Put that equation in a square root.

User Ernests Karlsons
by
5.5k points